Peran Etika Profesi dalam Membentuk Calon Guru Matematika UIN K.H. Abdurrahman Wahid Pekalongan yang Profesional dan Berkarakter - Rizkiyya Ramadhani; Selsa Yulianingsih; Jihan Ulayya; Muhammad Iqbal Nashrulloh (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study examines how prospective mathematics teachers view professional ethics in shaping their character and professionalism, particularly in addressing educational challenges in the digital age. The study argues that professional ethics serves as an important moral foundation, not merely an administrative rule. Using a descriptive qualitative approach, semi-structured interviews were conducted with mathematics education students at UIN KH. Abdurrahman Wahid Pekalongan who had completed a professional ethics course. Prospective teachers viewed professional ethics as a foundation for identity formation that fosters objectivity, pedagogical responsibility, honesty, patience, and empathy. However, implementation in the field faces several challenges, including suboptimal emotional management in the classroom, the still-abstract nature of mathematics delivery, and technological-structural issues. This study is still limited to prospective teachers from one Islamic state university, thus limiting broader generalizations. Pragmatically, this implies that mathematics teacher training must design professional ethics courses contextually and reflectively, bridging abstract pedagogical ethical values ​​with the realities of the digital-age classroom.